UPAYA PENINGKATAN KESEHATAN PADA USIA LANJUT DI MASA PANDEMI COVID-19 - Wijayanti, Lumastari Ajeng; Nurseskasatmata, Satria Eureka (Jurnal Abdi Masyarakat, 2023)
Communities around the world have been living with pandemic conditions for more than a year. the elderly are still the largest contributor to death, although only 11.3% of all positive cases. These conditions indicate that efforts to deal with Covid-19 are very necessary for the elderly. Identifying the knowledge and health of the elderly in an effort to improve health in the elderly during the COVID-19 pandemic. This research uses an educational method with lectures and questions and answers about Smart Seniors. Education is carried out by providing counselling and health consultations based on the results of examinations (blood pressure,  cholesterol, uric acid and blood sugar) for the elderly concerned. Leaflets about SMART seniors were also given, so that the material was easy to remember and could be distributed to other elderly  people or the surrounding community. Participants in this Community Service activity were attended by 64 elderly people, the community was very active in participating in these activities and this was reflected in the attendance of 95% of participants and participating in this activity until it was finished, as well as the enthusiasm of the participants or the elderly who consulted about the results of blood pressure checks , blood sugar levels and individual uric acid levels This Community Service Activity was held in Jemekan Village, This activity was greeted with great enthusiasm by the elderly  participants because it was the first time a medical examination and consultation was held by the  Abdurrahman Ibrahim Jemekan Foundation with POLKESMA Lecturers.